P11.01 TMZ-LEV- IFN cocktail regimen significantly inhibited the growth of glioma. (6th September 2019) - Ni, X; Qu, Y; Wang, J; Chen, F; Cai, H; Yu, Y; Yu, Y; Yu, Z; Cen, Z; Chen, Z
Abstract: BACKGROUND: TMZ, is the first line chemotherapeutic drug for glioma, and drug resistance is one of the most important reasons for glioma treatment failure. Our previous studies have found that: 1) Type I interferon (IFN) could reverse the resistance of TMZ by inhibiting NF-κB activity, and down-regulating the expression of MGMT in vivo and in vitro; 2) IFN-α could significantly improve chemtherapeautic effect of TMZ for GBM patients. We aim to investigate the therapeutic effect of a cocktail chemotherapy regimen combining temozolomide (TMZ)- Levetiracetam(LEV) - interferon (IFN) on human glioma U138 and U251 subcutaneous xenograft tumor. MATERIAL AND METHODS: 30 xenograft tumors were established by subcutaneously injecting 1×106 glioma cells into the right flank of 4-week-old female BALB/C nude mice and then randomly divided into 5 groups (n=6/group): Control group; TMZ group; TMZ+IFN group; TMZ+LEV group; TMZ+LEV+IFN group. Anti-tumor efficacy of five regimens for tumor-bearing mice was tested after treatment with TMZ (50 mg/kg, i.p.), IFN (2×105 IU, s.c.), LEV (150 mg/kg, i.p.), while TMZ dose were reduced to 12.5 mg/kg for U251 tumors. All drugs are given once a day for five consecutive days. After therapy, the size of tumor was measured every day until the control tumors reached 2000 mm3. Mice bearing U138 tumors were sacrificed at 40 days after therapy, and mice bearing U251 tumors were killed at 26 days after therapy. RESULTS: We identified that both U138 and U251 tumor growth among TMZ group, TMZ+IFN group, TMZ+LEV group and TMZ+LEV+IFN group were significantly inhibited (P<0.05), compared with the control group. Tumor weight of all treating group was lower than that of the control group (P<0.05). The tumor weight of TMZ+LEV+IFN group was the lowest and significantly lower than that of TMZ+LEV group and TMZ group (P<0.05, respectively). No significant difference was found between TMZ+LEV+IFN group and TMZ+IFN group in U251 subcutaneous xenograft tumors, although the tumor weight was lower in TMZ+LEV+IFN group (P>0.05). In the treatment of mice bearing U138 glioma, TMZ+LEV+IFN regimen was significantly superior to TMZ+IFN regimen. CONCLUSION: Our data demonstrate that both IFN and LEV can sensitize TMZ effect on glioma. TMZ-LEV-IFN cocktail appears the best regimen.